2018
DOI: 10.1016/j.enconman.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The maximum theoretical performance of unconcentrated solar photovoltaic and thermoelectric generator systems

Abstract: The maximum efficiency for photovoltaic (PV) and thermoelectric generator (TEG) systems without concentration is investigated. Both a combined system where the TEG is mounted directly on the back of the PV and a tandem system where the incoming sunlight is split, and the short wavelength radiation is sent to the PV and the long wavelength to the TEG, are considered. An analytical model based on the Shockley-Queisser efficiency limit for PVs and the TEG figure of merit parameter zT is presented. It is shown tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Bjørk et al [53] studied the maximum theoretical performance of a PV/TEG system without concentration. The authors used an analytical model to study the performance of the system and found that the hybrid system using spectrum splitting could achieve a maximum efficiency increase of 1.8% point compared to the PV only system.…”
Section: Spectrum Splitting Methodsmentioning
confidence: 99%
“…Bjørk et al [53] studied the maximum theoretical performance of a PV/TEG system without concentration. The authors used an analytical model to study the performance of the system and found that the hybrid system using spectrum splitting could achieve a maximum efficiency increase of 1.8% point compared to the PV only system.…”
Section: Spectrum Splitting Methodsmentioning
confidence: 99%
“…The findings show improved system performance by 2.67% and 2.19%, respectively, at 30 and above concentration. Bjørk and Nielsen (2018) analysed the optimal mathematical efficiency of a concentration-free PV-TEG system. They adopted an empirical approach during the research, and the results showed that a peak efficiency gain of 1.8% could be achieved using spectrum splitting in the hybrid system.…”
Section: Spectrum Splitting Techniquementioning
confidence: 99%
“…The TEG is independent of the PV Bjørk and Nielsen (2018) The work was done using the analytical model by adopting the spectrum splitting method.…”
Section: Control Experiments and Simulationmentioning
confidence: 99%
“…The results prove that the new hybrid module has a 25% better efficiency than just the PV cell. One theoretical work, conducted by Bjørk and Nielsen [10], proposed a combined system where the thermoelectric elements are mounted directly on the back of the PV panel, and a tandem system, where the incoming radiation is split, with the short wavelength radiation sent to the PV and the long-wavelength delivered to the thermoelectric set. The maximum increase in efficiency was 4.5% for the combined case and only 1.8% for the tandem design.…”
Section: Introductionmentioning
confidence: 99%